2011 IEEE/RSJ International Conference on Intelligent Robots and Systems 2011
DOI: 10.1109/iros.2011.6095136
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic considerations for anthropomorphic wrist exoskeletons: A simulation study on the effects of joint misalignment

Abstract: This work focuses on anthropomorphic exoskeletons for the human wrist. We consider a 2 dof model for the human wrist with non intersecting joints and a similar model for the exoskeleton. We assume a viscoelastic attachment between the human hand and the handle of the exoskeleton which on one side allows the different kinematics of the exoskeleton to follow the human wrist and, on the other side, induces reaction forces at all joints, in particular causing discomfort. We quantify discomfort as the amount of pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The complexity of interaction between exoskeleton structure and human body is a major issue that requires attention. The incorrect alignment between exoskeleton and human upper limb makes patients uncomfortable when they are given therapy [115][116][117][118][119]. The intensity of uncomforting caused by tissue depression varies from annoying to pain depending there are a few which is being used for rehabilitation program and are commercially available.…”
Section: Joint Alignment With Human Anatomymentioning
confidence: 99%
“…The complexity of interaction between exoskeleton structure and human body is a major issue that requires attention. The incorrect alignment between exoskeleton and human upper limb makes patients uncomfortable when they are given therapy [115][116][117][118][119]. The intensity of uncomforting caused by tissue depression varies from annoying to pain depending there are a few which is being used for rehabilitation program and are commercially available.…”
Section: Joint Alignment With Human Anatomymentioning
confidence: 99%
“…These pads cause an increase of distance between the palm and the back side of the handle resulting in misalignment on the RUD. This misalignment would make the exo uncomfortable [2]. Conditions ii and iii were conducted underneath two scenarios:…”
Section: B Protocolmentioning
confidence: 99%
“…Human-machine interaction, a central topic in the field of robotic exoskeletons, necessitates consideration of ergonomy, and ergonomic constraints have recently become prevalent in the early stages of exoskeleton design methodologies [1], [2]. Exoskeletons are broadly divided into anthropomorphic and non-anthropomorphic types.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, recent studies have found that misalignment between the two joints happens in many cases [5][6][7] causing hyperstaticity and unwanted force around them. [8][9][10] This affects the safety of the operator, especially the one with gait disabilities. 11 One of the reasons why aligning them is difficult to attain is that the human joints are mostly not simple hinges and have both rotational and translational degree of freedom (DOF) at the same time.…”
Section: Introductionmentioning
confidence: 99%